(untitled) (Journal of Scientific Research, 2020)
The study area Burutu lies within the transitional environment of the Niger delta. The area is sectioned by a compact network of rivers and creeks, which maintain a fragile but dynamic balance between saline, estuarine and freshwater surface bodies. Twenty direct current resistivity soundings were carried out to provide adequate information on the spatial lithological variation and groundwater conditions in Burutu. Resistivity contrasts and water analysis were used as a means of characterizing probable lithology and water type present within the pore spaces of aquiferous units. The results revealed spatial development of the aquifer architectural facies that follows a trend of mostly sand with little clay in the south to sand with abundant of clayey facies in the north near the Forcados River. The groundwater conditions indicated that salty/brackish water constituting about 4 % of water present was confined to the bank of the Forcados River and extend laterally landwards to about 120 m. Further away from the river bank, the water was mostly poor to good quality freshwater. The depth to the freshwater constituting about 96 % groundwater present varied from about 49.0 – 63.3 m near the Forcados River and became as shallow as 1.6 m in inland areas.